2023
DOI: 10.5694/mja2.52063
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pathogenesis and spectrum of neurological symptoms in COVID‐19 and post‐COVID‐19 syndrome: a narrative review

Robb Wesselingh

Abstract: Summary Neurological symptoms are not uncommon during severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and reflect a broad spectrum of neurological disorders of which clinicians should be aware. The underlying pathogenesis of neurological disease in coronavirus disease 2019 (COVID‐19) may be due to four mechanisms of nervous system dysfunction and injury: i) direct viral neurological invasion; ii) immune dysregulation; iii) endothelial dysfunction and coagulopathy; and iv) severe syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 93 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…There is a growing body of evidence of neurological manifestations of COVID-19, and therefore, understanding the mechanisms of SARS-CoV-2 neuropathology will have a significant impact on treatment strategies. Neurological sequelae in COVID-19 patients are diverse and include headache, encephalitis, vasculopathy and vasculitis including stroke, haemorrhage and cerebral thrombosis [20]. The underlying mechanism by which SARS-CoV-2, directly or indirectly, causes these manifestations is currently unclear, and there may be multifactorial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing body of evidence of neurological manifestations of COVID-19, and therefore, understanding the mechanisms of SARS-CoV-2 neuropathology will have a significant impact on treatment strategies. Neurological sequelae in COVID-19 patients are diverse and include headache, encephalitis, vasculopathy and vasculitis including stroke, haemorrhage and cerebral thrombosis [20]. The underlying mechanism by which SARS-CoV-2, directly or indirectly, causes these manifestations is currently unclear, and there may be multifactorial mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism by which SARS-CoV-2, directly or indirectly, causes these manifestations is currently unclear, and there may be multifactorial mechanisms. Moreover, peripheral nervous system sequelae including Gullain-Barre syndrome, peripheral neuropathy and myopathy, likely due to severe pulmonary disease, have been reported [20,21]. Recently, medium-and long-term follow-up studies revealed an increased risk of dementia, migraine, Alzheimer's disease and other cognitive defects 12-24 months post-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with COVID‐19 may suffer from fever, sore throat, cough, diarrhea, sleep disorders, anxiety, depression, and cognitive impairment, which is associated with long COVID symptoms during recovery. 1 , 2 , 3 , 4 Despite some clinical trials of drugs to improve COVID‐19 symptoms, there remains no consensus on effective treatment methods, and immunocompromised elderly people and children need special attention. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%